Convex characterization of linearly convex domains - Nikolov, Nikolai; Thomas, Pascal J. (MATHEMATICA SCANDINAVICA, 2012)
We prove that a C^1,1-smooth bounded domain D in C^n is linearly convex if and only if the convex hull of any two discs in D with common center lies in D.